(untitled) (Economics and region, 2024)
The subject of this study is the global experience of digitalisation of market relations. Purpose and relevance of the topic. Digitalisation has a significant impact on the development of national economies and international relations and entails the need to review the experience of leading countries in the field of digitalisation of market relations. The purpose of the study is to review foreign experience (on the example of individual countries) of digitalisation of market processes. The article examines the world experience of digitalisation of market relations, the need and importance of formulating strategies for the development of digital technologies and state support for the regulation of digitalisation processes. The study is based on the fundamental works of domestic and foreign scholars on the basics of digitalisation regulation. The study is based on a general scientific methodology and a systematic approach to problem solving. Results. The key directions of regulation of digitalisation of market relations in the USA, EU, Japan, China, Singapore are considered. It is emphasised that today governments can create reliable hardware and software solutions for the national digital economy through well-developed laws and international agreements for the global digital economy. Common problems of digitalisation and promising directions are outlined. It is determined that the solution to these problems is primarily in the field of legal regulation of the digital economy. Practical value of the article. Systematisation of the accumulated world experience, consideration of the processes of formation and regulation of the development of the digital economy. Having looked at the development of the digital economy in the wired countries, their development of the main digital transformation programs has made it possible to accumulate knowledge about the improvement of digital transformation processes coming from foreign sources. Today, nutritional regulation of the cyberspace and digital environment, professional training of frontline workers, and adjustment of business processes arising from the digitalization trend are no longer relevant.